Impact of drought stress on basal stem rot (BSR) disease development in oil palm seedlings - Saipol Anuar, Mohd Amar Shafiq; Nusaibah, Syd Ali; Neoh, Bee Keat (Springer, 2024)
Oil palm is the most prominent high-yielding multipurpose oil crop available to date. Malaysia is ranked as the second largest producer of palm oil products (28), after Indonesia (57), with more than 21.2 million metric tonnes of production in 2019. The increasing demand for palm oil products leads to various research and developments to enhance palm yield. Unfortunately, climate change that results in drought affects the commodity crop directly. In addition to drought, a devastating catastrophe hampering the Malaysian oil palm is basal stem rot (BSR) disease. Therefore, the interactions between these two stresses were investigated under nursery experiments to foresee their impacts on the oil palm industry. The experiment revealed that combined stresses on oil palm seedlings had the greatest impact when compared to single-stress seedlings. In terms of peroxidase (PO), polyphenol oxidase (PPO) and total phenolic compound (TPC) induction, which have been identified as biochemical defenses against biotic stress, were not interrupted by drought stress except for the induction of the PPO enzyme. While the proline level was interrupted by basal stem rot (BSR), demonstrating an overcoming factor of the drought stress in BSR-diseased seedlings.